(3dbWI GdaQGFO aj JMbjb GdahGFOs - (3TgGH GdOjf CHi GdYHGS CMeO Hf eMeO Hf CMeO Hf Ydj Hf YHO GdQMef Hf CHi GdYGajI GdecfGSis; (3GHf GdNWjH GdbSfWjfjs
(3ChdgG (B:s
(3GdMeO ddg Pi GdHbGA hGdbOe s
(3Cdag ddSdWGf CHh GdYHGS GdefUhQs
(3hLeY ajg JQLeI ef hLO ef Chd SfI (B801(3Edi SfI (B810 (3ddgLQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdJGQjNs